A computerized pharmaceutical repurposing approach reveals Semicochliodinol B synthesized from Chrysosporium merdarium as a viable therapeutic contender for Marburg virus's VP35 and VP40 proteins. (2022) - Hasan, Mahamudul; Mia, Md Mukthar; Islam, Md Mazharul; Hasan Saraf, Md Sawkat; Islam, Md Shariful
Abstract: The Marburg virus (MV) is a highly etiological agent of hemorrhagic fever in humans and has spread across the world, including America, Australia, Europe, and other Asian countries. MV is responsible for the occurrence of the most dangerous known human diseases, with previous outbreaks demonstrating high pathogenicity and a human death rate of (23–90) %. Despite the discovery of MV over 50 years ago, there are no licensed preventative or therapeutic countermeasures available. Besides, this virus frequently counteracts immune responses through multifunctional VP35 and VP40, which are required for viral RNA synthesis, assembly, and structure; thus, these two proteins are possible therapeutic targets. To develop candidate therapeutics, different natural products containing bioactive compounds are a suitable option. In addition, bioactive substances with antiviral activity are found in traditional plants such as mushrooms. Thus, we used a systematic screening technique to identify the best candidates for VP40 and VP35 inhibitors, as well as to anticipate potential treatment possibilities for developing MV. Finally, the results of the present study suggest that Semicochliodinol B, found in mushroom-derived fungi, was the best inhibitor. The predicted drugs based on the ligand, benzonatate (DB00868), mycophenolate mofetil (DB00688), gallamine triethiodide (DB00483), capreomycin (DB00314), and latamoxef (DB04570) could be exploited and developed as an alternative or complementary therapy for the treatment of MV.